Letter - Lizaso, Jose I. de
026-0082-001 Euzkadi Ordezkaritza Basque Delegation, 14, Eccleston Square, London, S.W.1. Tel: Victoria 0926. 30th May, 1939. Dear Sir Walter, I want to thank you for your letter of May 25th, and to say how very much we appreciate the efforts you have been taking with regard to the skilled Basque workers now in concentration camps in France. I fully appreciate, of course, the difficulties of such a matter but, nevertheless, hope sincerely that your present inquiries will be successful. With renewed thanks for your great kindness and interest in the welfare of our workers. Yours sincerely, Jose I. de Lizaso Sir Walter Citrine, K.B.E. Trades Union Congress, Transport House, Smith Square, S.W.1. 292/946/26/82